Time to care? The effects of retirement on informal care provision - Björn Fischer; Kai-Uwe Müller (Journal of Health Economics, 2020)
This paper analyzes the impact of women's retirement on their informal care provision. Using SOEP data, we address fundamental endogeneity problems by exploiting variation in the German pension system in two complementary ways. We find a significant effect of retirement on informal care provision, when using early retirement age thresholds as instruments. Heterogeneity analyses confirm the underlying behavioral mechanism, a time conflict between labor supply and informal care. We further exploit a sizable increase in the early retirement age for German women and find that affected women provide less non-intensive care. High intensity care is not impacted, which leads to a double burden and potentially negative health effects for caregivers. Exploiting the policy reform, we find evidence supporting the notion that formal care is no substitute for informal care. This implies that less overall care is received, which can be damaging to the health of the recipients of care.
Keywords: J22; J14; J18; J26; H43; H55; 330; Retirement; Informal care; Regression discontinuity; Age threshold; Pension reform